Avaliação institucional no ensino superior: aspectos instituintes - Musis, Carlo Ralph de (2006)
This work researched and reflected about the possibility of developing a process of evaluation in Higher Education Institutions by the meanings developed by the people who belong to them. At first, the construction of this process implies in the interpretation of the Higher Education Institutions as a group that is at the same time formal, contradictory and dialogic. In the conceptual plan, the concept of judgment and enlightenment was developed in Immanuel Kant e Hannah Arendt s perspective, followed by the reflections done by Theodor W. Adorno to the Kantian categorical imperative. Finally, the sociological model developed by Pierre Bourdieu was used to understand the complex that the individuals that are being studied use to structure their actions, defined the line that would be followed in this evaluation and, according to the specificities of the locus, demanded the use of different instruments, in this case: questionnaires, observation and interviews (individually and in group). Analyses of the content based on associated and implicative figure, multidimensional stagger and non parametric correlation were done. From this comparison a statement was made that the Higher Education Institution used in the research had a behavior in which the heteronomy, on the one hand, establishes components that make the educational process more difficult and spreads discourses guided by the clichés, and on the other hand, shows a complex with potential for the free knowledge and practices